Human bite facial wounds in Bouaké (Côte d'Ivoire): development of a therapeutic algorithm in underdeveloped countries - Zegbeh-N'guessan Eric Kouassi; Bérété Pornan Issa Jules; Salami Tahib Arnaud; Assouan Camille; Assi Yapo Romaric Evrard; Crezoit Grébéret Emmanuel (EDP Sciences, 2020)
Introduction: The treatment of facial wounds by human bites is difficult, especially in under-developed countries. We aimed to distinguish the epidemiological and clinical aspects to describe the therapeutic methods and evaluate their effectiveness. Materials and methods: This was a descriptive and retrospective study over a period of 6 years. Patients who consulted regarding a human bite wound and were surgically treated were included. Results: Eighteen patients with a hospital prevalence of 0.008% were enrolled. The ratio of men to women was 2 (12 men for every 6 women). The average age was 32.77 years (range, 23-45 years). The lesions were labial in 11 cases (61.11%). The wounds were type III in eight cases (44.44%) and type II in nine cases (50%). Surgical treatment was primary in 12 cases (66.67%) and delayed in 6 cases (33.33%). The evolution was favorable in 16 cases (88.89%). Discussion: The wounds on the face created by human bite can be effectively treated via primary repair while reserving systematic secondary closure to an initially necrotic wound.